Pengaruh Pendidikan Pemilik, Pemahaman Akuntansi, dan Motivasi Pemilik Terhadap Penerapan Standar Akuntansi Keuangan Untuk Entitas Tanpa Akuntabilitas Publik (SAK ETAP) (Studi Empiris: Perusahaan Kecil dan Menengah di Kota Tangerang) - Rinny Meidiyustiani (UNSIKA (Universitas Singaperbangsa Karawang), 2016)
The objective of this research is to reveal the empirical evidence on the influence of owner’s education, of accounting comprehension, accounting practice, and owner’s motivation towards the implementation of SAK ETAP at SMEs in Tangerang City partial and simultaneous. The populations in this research are the owners of SMEs located in Tangerang City. Data sampling is conducted using the method of convenience sampling on 50 owners. Data is collected based on questionnaire distributed to the owners of SMEs in Tangerang City. Analysis is run on data which have been tested for validity and reliability. The analysis process is done using double linier regression analysis technique. The results show as follows: the owner’s education variable does not affect on the implementation of SAK ETAP; accounting comprehension variable does not affect on the implementation of SAK ETAP; either partially or respectively. Meanwhile, the owner’s motivation variable do not affect on the implementation of SAK ETAP. However, the owner’s education, of accounting comprehension, accounting practice, and owner’s motivation variables do significantly influence the implementation of SAK ETAP simultaneously.